Security Concepts in Smart Cities - Karatürk, Ebru; Koçyiğit, Emre (IEEE, 2020)
Both the population growth in the world and the number of people living in the city are increasing day by day while the rural population decreases. However, lack of resources, limited sources or difficulties in city life also arise. In response to these situations, the Smart City concept emerges and thanks to this concept, which integrates information and communication technology, it optimizes the available resources and makes people's life more qualified, efficient and comfortable. Smart cities include the phases of transferring, storing and processing real-time data from sensors and manage variable subsystems. While the transactions are carried out successfully for the purposes, the security and privacy problems must be examined carefully. In this paper, we analyze security issues and challenges in two ways: IoT-based and cloud-based. And as a solution proposal, it is stated that we can use authentication, encrypted communication, and blockchain to ensure data privacy. It is difficult to provide security in smart city architectures due to its decentralized and distributed structure with the existing technology IoT. Blockchain offers a security approach with a decentralized and distributed structure.
2nd International Congress on Human-Computer Interaction, Optimization and Robotic Applications (HORA)
Keywords: Blockchain; Data Privacy; Internet-of-Things (IoT); Smart City; Cloud; Cyber Security